Cyclic microwave-assisted synthesis of flower-like and hexapod silver bismuth sulfide - Titipun Thongtem (2018)
Nanostructured AgBiS2with the shapes of flowers and hexapods was successfully produced from AgNO3, BiCl3and sulfur sources (thioacetamide and thiourea) in ethylene glycol, by a cyclic microwave process. The phase was detected using X-ray diffraction (XRD) and selected area electron diffraction (SAED). Their SAED patterns were also in accordance with those of the simulations. Scanning and transmission electron microscopies (SEM and TEM) revealed the gradual transformation of nanostructured flowers into nanostructured hexapods, due to the microwave power increases. Their photoluminescence (PL) emissions were detected at the same wavelength of 435 nm, although they were produced under different conditions. © 2009 Elsevier B.V. All rights reserved.